Physico-chemical and microbiological assessment of drinking water of the selected restaurants in Mymensingh district of Bangladesh (Progressive Agriculture, 2022)
Water is essential for living organisms for their survival. Access of adequate and safe water is a basic need of human beings. In adequacy and unsafe water supply may cause various health problems. This study was designed with a view to assessing physicochemical properties of drinking water collected from different restaurants at Mymensingh sadar. In this case, electrical conductivity (EC), total dissolved solids (TDS), pH, dissolved oxygen (DO), biological oxygen demand (BOD), arsenic (As), iron (Fe) and lead (Pb) were measured. Furthermore, Microbiological assessments of drinking water samples were carried out. For achieving the microbiological assessment, methods of heterotrophic plate count (HPC) and total coliform count (TCC) were applied. The mean value of EC, TDS, pH, DO, BOD, As, Fe, Pb were 682.38 µS cm-1, 201ppm, 7.11, 4.98 mg/L, 1.72 mg/L, 0.005 ppm, 0.181 ppm and 0.000 ppm, respectively. According to the standard of drinking water the EC, TDS, pH, DO, BOD, As, Fe, Pb toxicity were not detected in all samples. All of above mentioned parameters were present in water within permissible limits. In most cases the concentrations of Pb and in some cases the concentrations of Fe were considered as toxicants due to the higher concentrations noted. The highest heterotrophic plate count was found in water of Ganginapar sample (1.2×107 CFU/ml) and the highest total coliform count was noted in C. K. Ghosh road sample (13 coliforms/100 ml). Therefore, the examined water quality parameters indicate that water quality of the restaurants at Mymensingh sadar is suitable for drinking. Although some of the samples identified as the presence of fecal coliforms that indicates contamination of feces with water. One sample among the studied drinking water samples was contaminated with fecal coliform which is very harmful for health and this water is not suitable for drinking. It may be concluded that hygienic and quality water need to supply for human drinking purposes.Progressive Agriculture 32 (2): 84-95, 2021